2021
DOI: 10.3233/wor-210525
|View full text |Cite
|
Sign up to set email alerts
|

How anxious were Quebec healthcare professionals during the first wave of the COVID-19 pandemic? A web-based cross-sectional survey

Abstract: BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic may cause significant anxiety among healthcare professionals (HCPs). COVID-19-related psychological impacts on HCPs in Western countries have received relatively little attention. OBJECTIVE: This study aims to assess the levels of anxiety in HCPs working in the province of Quebec (Canada) during the first wave of the COVID-19 pandemic and identify factors associated with changes in anxiety scores. METHODS: An exploratory online cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with studies in which differences between men and women have been observed in critical care residents in CPR simulation scenarios [ 39 ]; in extreme conditions, gender differences have been observed after CPR simulations, with a higher level of anxiety in women [ 28 ]. During the first wave of the COVID pandemic, an increase in anxiety in female health professionals was evidenced [ 40 , 41 , 42 , 43 , 44 , 45 ]. Concurrently, other studies with undergraduates have shown higher levels of trait anxiety in women [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with studies in which differences between men and women have been observed in critical care residents in CPR simulation scenarios [ 39 ]; in extreme conditions, gender differences have been observed after CPR simulations, with a higher level of anxiety in women [ 28 ]. During the first wave of the COVID pandemic, an increase in anxiety in female health professionals was evidenced [ 40 , 41 , 42 , 43 , 44 , 45 ]. Concurrently, other studies with undergraduates have shown higher levels of trait anxiety in women [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The environment in vaccination sites can be made more calming or comforting to ease people's anxiety in healthcare environments. Young and inexperienced healthcare professionals in Canada, for instance, experienced high levels of anxiety at the beginning of the pandemic [82]. One of the few applications of AD in the healthcare environment investigated the desired affective qualities of primary health care environments [83].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%